PERKEMBANGAN SEJARAH AKUNTANSI DI INDONESIA - Dwi Urip Wardoyo; Naufal Zuhdi; Junero Abelio (Universitas Sains dan Teknologi Komputer, 2023)
Accounting is a tool for measuring and informing the financial results of a company or business to people who need it both inside and outside the company. The results are described using accounting reports or financial reports. The public stigma about new accounting history regarding the study of accounting history generally criticizes the approach used by traditional accounting history which is said to be ahistorical and antique (Sukoharsono, 1998a). It is said to be ahistorical because the history of accounting is written with a present point of view, where accounting history tends to be presented chronologically by slowly displaying present truths. And it is said to be antique because the history of accounting is concentrated on explaining